Case report: Successful therapy with recombinant human vascular endostatin in an elderly man with colon telangiectasia and idiopathic thrombocytopenic purpura - Wu, Yushan; Jia, Yongbin; Jiang, Mingshan; Zhang, Hu (Frontiers in Medicine, 2025)
An 83-year-old male presented to our Digestive System Department with a 5-day history of severe gastrointestinal (GI) bleeding and a 14-year history of idiopathic thrombocytopenic purpura (ITP) with low platelet levels. Colonoscopy revealed extensive telangiectasias throughout the colon, particularly in the transverse and ascending segments. Standard treatment with proton-pump inhibitors and somatostatin proved ineffective. Additionally, conventional therapies such as estrogen and thalidomide were contraindicated due to the comorbidity of ITP. Endoscopic hemostasis was also difficult to perform because of the widespread nature of the lesions. However, after the innovative use of four courses of recombinant human vascular endostatin (Endostar) therapy, the colon telangiectasia was completely resolved, and the patient reported no GI bleeding for 2 years. Managing severe GI bleeding with a rare etiology is particularly challenging, especially in patients with contraindications to conventional treatments due to comorbidities. In this case, a vascular endothelial growth factor (VEGF) inhibitor was successfully applied to treat a refractory and rare GI bleeding, which may offer a novel therapeutic approach for similar cases.